Kinematic Decomposition of the H i Gaseous Component in the Large Magellanic Cloud - Se-Heon Oh; Shinna Kim; Bi-Qing For; Lister Staveley-Smith (The Astrophysical Journal, 2022)
We perform a profile analysis of the combined H i data cube of the Large Magellanic Cloud (LMC) from observations with the Australia Telescope Compact Array and the Parkes radio telescope. For the profile analysis, we use a newly developed algorithm that decomposes individual line profiles into an optimal number of Gaussian components based on a Bayesian nested sampling. The decomposed Gaussian components are then classified into kinematically cold, warm, and hot gas components based on their velocity dispersion. The estimated masses of the kinematically cold, warm, and hot gas components are ∼12.2%, ∼58.3%, and ∼29.5% of the total H i mass of the LMC, respectively. Our analysis reveals the highly complex H i structure and kinematics of the LMC that are seen in previous studies but in a more quantitative manner. We also extract the undisturbed H i gas bulk motions and derive new H i gas bulk rotation curves of the LMC by applying a 2D tilted-ring analysis. In contrast to previously derived H i rotation curves, the newly derived bulk rotation curves are much more consistent with the carbon star kinematics, with rotation velocity linearly increasing in the inner part and reaching a maximum of ∼60 km s ^−1 at the outermost measured radius. By comparing the lower bulk rotation curves with previous studies, we conclude that there is a lower dynamical contribution of dark matter in the central part of the LMC.